Opportunities vis-Ã -vis threat to thermal genera-tion due to rising renewable energy penetration - Tiwari, Shubham; Dwivedi, Bharti; Dave, M.P (International Journal of Engineering and Technology, 2017)
An effort has been made to access what happens to prevailing thermal generation plants if the generation from renewable energy resources is increased above 20% of total generation. A test case has been taken where generation system comprising of ten thermal generating units is in conjunction with a 500 MW Wind Energy generation plant, and a 500 MW Solar Energy generation plant. It has been found that on one hand the cost of generation gets significantly reduced whereas, on the other hand few thermal generators are compelled to remain with no generation at all. The study reveals the peak load shaving and the economy achieved in overall generation system versus the threat to individual thermal generating plant due to inclusion of nearly 23% generation from renewable resources.